Pengaruh Latihan Resitance Band Terhadap Kecepatan Tendangan Sabit Pada Atlit Pencak Silat Club Padepokan Elang Al Qausar Kota Kendari - Widyawati Togala, Basman, Resky Ana Abadi (Jurnal Ilmu Sosial Dan Pendidikan, 2024)
The purpose of this research is to determine the effect of resistance band training on the speed of sickle kicks in pencak athletes at the Padepokan Elang Al Qausar Club, Kendari City. 1.3 Benefits of research. The research population was all Pencak Club Padepokan Elang Al Qausar athletes, Kendari City, consisting of 11 men and 9 women. The sample in this study was the entire population, totaling 20 pencak silat athletes. pull using total sampling technique. The research instrument used for data collection in this research was a test. The sickle kick speed technique uses peaching and to determine the kick speed in the form of a value (score), the kick test is carried out 2 times with a time of 10 seconds. Based on data analysis, the results of the research show that there is an influence and a significant value of Sig. (2-tailed) 0.000 < 0.005 indicates that there is a significant difference between the initial variable (Pretest) and the final variable (posttest). This shows the influence of training using Resistance Bands on sickle speed kicks in pencak silat martial arts.